Hetero-Ligand peptide functionalization of gold nanoparticles for selective detection of cobalt (II) ions - Jamadon, Nur Khaliesah (2022)
Cobalt (II) ions, Co2+ represents one of the heavy metals that poses contamination to the environment. Despite being an essential element, over exposure to Co2+ can be detrimental to human health. To combat Co2+ contamination, monitoring the level of Co2+ with a fast detection technique is of utmost importance. Current techniques for Co2+ detection such as inductively coupled plasma spectroscopy, atomic absorption spectrometry and voltammetry are sophisticated, expensive, and laboratory bound. Thus, to overcome this, nanomaterials was often used as probe for the development of colorimetric detection approach due to its simplicity, rapidity, and effectiveness. This research focusses on exploiting the gold nanoparticles (AuNPs) with unique plasmon surface property. The approach involves functionalizing the AuNPs with hetero-ligand peptide owing to its excellent capability for metal ion detection. Herein, the successful functionalization of AuNPs were achieved with the integration of a mono- (GCH-AuNPs and HCH-AuNPs respectively) and heteroligand peptide (GCH+HCH-AuNPs). Both peptide ligands were synthesized using solid phase synthesis approach. As both surface ligands of AuNPs formed complexes with Co2+, the synergistic effect of hetero-ligand peptide exhibits excellent colorimetric sensing performances where the sensor produced a color change from red to blue could be observed by the naked eye and UV–visual spectroscopy. There is a shift from 530nm (red) to 660nm (blue) which arises from aggregation effect of the AuNPs. The colorimetric sensing using heteroligand was selective towards Co2+ at as low as 100 ppb level. The colorimetric sensing towards Co2+ also achieved a linear detection range from 100-1000 ppb (R2 =0.9433) with detection limit was calculated to be at 300 ppb level. The characterization and comparison of the mono-ligand and hetero-ligand system was also supported by the analysis of dynamic light scattering and transmission electron microscope to determine the changes in size of 20 nm AuNPs when exposed to Co2+. This study have demonstrated a great potential of exploiting mixed ligand peptide on nanomaterials in improving the performance of colorimetric sensor of metal ions with high selectivity and sensitivity.